VOLATILIDAD DE LOS COMMODITIES MINEROS Y SU INCIDENCIA EN LA ECONOMÍA NACIONAL - Gomero Gonzales, Nicko Alberto (2017)
The mining commodities market is anchored to the behavior of the global economy, especially to countries like China and the United States configured as the first economic powers in this globalized world. The fact that the Peruvian economy partly shows a high sensitivity to the price of export minerals opens spaces of vulnerability to the market oscillations of this type of products. These effects will be appreciated in the real and financial sector of the economy. Therefore, through the correlation method, we can determine and explain the relationship between the price of commodities and the main macroeconomic accounts, a result that will show the degree of dependence of the economy on this type of market. The study also highlights the importance of emerging countries, including China, as the main demander and producer of these types of commodities, whose strengths are relevant factors in the dynamism of this market.